2021
DOI: 10.3390/ijms22115451
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Hyperferritinemia Cataract Syndrome: Ferritin L Gene and Physiopathology behind the Disease—Report of New Cases

Abstract: Hereditary hyperferritinemia-cataract syndrome (HHCS) is a rare disease characterized by high serum ferritin levels, congenital bilateral cataracts, and the absence of tissue iron overload. This disorder is produced by mutations in the iron responsive element (IRE) located in the 5′ untranslated regions (UTR) of the light ferritin (FTL) gene. A canonical IRE is a mRNA structure that interacts with the iron regulatory proteins (IRP1 and IRP2) to post-transcriptionally regulate the expression of proteins related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…The CAGUGU sequence within the IRE is a non-coding sequence that is highly conserved, and this sequence was found to have an important role in IRP-IRE binding [9][10][11][12]. c.-160A>G mutation in this sequence was identified in 17 patients from six families from Kayseri and Nevşehir in Turkey and claimed to be the most prevalent mutation causing HHCS in Turkey [12].…”
Section: Discussionmentioning
confidence: 99%
“…The CAGUGU sequence within the IRE is a non-coding sequence that is highly conserved, and this sequence was found to have an important role in IRP-IRE binding [9][10][11][12]. c.-160A>G mutation in this sequence was identified in 17 patients from six families from Kayseri and Nevşehir in Turkey and claimed to be the most prevalent mutation causing HHCS in Turkey [12].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, mutations in highly conserved regions may have deleterious effects on these biological functions. For example, the substitution of adenine to guanine in CAGUGU, a highly conserved motif in the 5′‐untranslated region of the ferritin light chain results in hereditary hyperferritinemia‐cataract syndrome 23. This mutation prevents the formation of a crucial harpin which ensures the recognition and interaction between the RNA and the iron‐responsive element‐binding protein at low iron concentrations 23.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the substitution of adenine to guanine in CAGUGU, a highly conserved motif in the 5′-untranslated region of the ferritin light chain results in hereditary hyperferritinemia-cataract syndrome. [23] This mutation prevents the formation of a crucial harpin which ensures the recognition and interaction between the RNA and the iron-responsive element-binding protein at low iron concentrations. [23] Similarly, our in silico FCHSD1_RNA structure analyses showed that the FCHSD1 R183W variant causes a change in both the secondary and tridimensional structures of FCHSD1_RNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The multiple functions of ferritin are evident by the binding of numerous transcription factors to the Fth1 gene promoter, e.g., activator protein 1 (AP-1 – involved in the regulation of cell growth, differentiation, and apoptosis), GATA-binding factor 1 (GATA-1 – involved in erythroid development), growth factor independent 1 transcriptional repressor (GFI1 – activated in hematopoiesis and oncogenesis), and HSF2 (promoting the expression of heat shock response genes) (based on www.genecards.org ). Mutations (e.g., deletions and single nucleotide polymorphisms (SNPs)) in 5′-UTR regions that disrupt the protein-promoter interactions in the IRE sites lead to the dysregulation of serum ferritin levels and the development of the hereditary hyperferritinemia cataract syndrome (Celma Nos et al, 2021 ). Recently, the regulation of ferritin chain translation independent of IRP-IRE has also been reported.…”
Section: Expression Of Ferritinsmentioning
confidence: 99%